2022
DOI: 10.1111/jocs.16713
|View full text |Cite
|
Sign up to set email alerts
|

Three centers experience with device closure of congenital Gerbode‐type perimembranous ventricular septal defects

Abstract: Objectives: We aim to evaluate our experience with interventional closure of Gerbode-type perimembranous ventricular septal defects (pmVSDs). Methods: We performed three-center retrospective data review of patients with congenital indirect Gerbode-type pmVSDs treated percutaneously between August 2017 and May 2021. Standard safety and latest follow-up outcomes were assessed. Results: Ten patients (six females) were identified with a median age of 6.8 years (range: 2.5-54) and a median weight of 26.5 kg (range:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…reported the first transcatheter closure of an acquired Gerbode defect. There are few published case reports and small series reports of immediate and short-term results following transcatheter closure of the Gerbode defect.Haddad et al9 in a retrospective multicenter study contribute their experience on percutaneous closure of the indirect Gerbode type pmVSD. Transcatheter closure was performed on 10 patients from three centers from August 2017 to May 2021.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…reported the first transcatheter closure of an acquired Gerbode defect. There are few published case reports and small series reports of immediate and short-term results following transcatheter closure of the Gerbode defect.Haddad et al9 in a retrospective multicenter study contribute their experience on percutaneous closure of the indirect Gerbode type pmVSD. Transcatheter closure was performed on 10 patients from three centers from August 2017 to May 2021.…”
mentioning
confidence: 99%
“…Haddad et al 9 in a retrospective multicenter study contribute their experience on percutaneous closure of the indirect Gerbode type pmVSD. Transcatheter closure was performed on 10 patients from three centers from August 2017 to May 2021.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Haddad et al (9) in a retrospective multicenter study contribute their experience on percutaneous closure of the indirect Gerbode type pmVSD. Transcatheter closure was performed on 10 patients from 3 centers from Aug 2017-May 2021.…”
mentioning
confidence: 99%
“…The authors then go on to comprehensively detail the risks and considerations of closing Gerbode-type defects, listing current literature available while aptly pointing out the lack of homogenized guidelines available when considering this type of pmVSD for transcatheter closure. Haddad et al (9) have effectively demonstrated that percutaneous closure of Gerbode type pmVSD's is a safe and effective alternative to surgical repair and is a valuable addition to the currently available literature available on this type of procedure Advances in echocardiography have allowed for accurate diagnosis and intra-procedure feedback with regards to optimal device size and device placement to prevent interference with the valves or the conduction system. Vijayalakshmi et al (10) in a series of 12 patients describe successful closure of their pmVSD with one patient developing transient complete heart block that resolved within 48 hours after administration of steroids.…”
mentioning
confidence: 99%